Physical activity levels and body composition in children living in disadvantaged areas of urban India - Forde, Cuisle (My University, 2010)
Background: Recent studies on children attending private or governmental schools in India have reported increasing rates of obesity. The aim of this study was to examine body composition and activity levels of children attending non-formal schools both in the community and in sheltered care. Methods: Sixty-five children were recruited. Anthropometric data was taken on all children. Activity levels of children residing in the community were assessed with accelerometers. Activity levels of girls living in sheltered accommodation were assessed using a questionnaire. Results: No child was obese. Thirty-two per cent were underweight. Higher rates of underweight were seen in the community children, and among females. Activity levels among those in sheltered accommodation were high, (mean of 15hours a week). Less than half the community dwelling children achieved the recommendation of 60 minutes moderate activity a day. Activities carried out consisted mainly of informal play. Children reported having little access to organised sport and physical education. Conclusions: Obesity was not seen in these subjects living in underprivileged areas in urban India. Children in sheltered accommodation reported meeting physical activity recommendations while objective results revealed that most children in the community did not. However, comparisons cannot be made between groups as methods of data collection differed.
PUBLISHED
Keywords: Obesity; Children; India; International Development; Health; Poverty